Defence Under Thatcher - Dorman, A. author. aut Link
XIII, 219 p.
Keywords: Drawing upon a wide range of interviews with many of the key actors, Andrew Dorman examines how defence policy was formulated and implemented during the premiership of Margaret Thatcher. This period witnessed major transformations in international and domestic politics, with defence emerging from its traditional postwar position of relative insignificance to become one of the key issues at the 1983 and 1987 general elections. Dorman provides a new understanding of policymaking by analysing defence policy in terms of three constituent parts: declaratory policy; military strategy and procurement policy.